Reproductive Health Information Application Using E-Mobile in Readiness to Face Menarche in Teenage Girls in East Jakarta - Syafar, Syafdewiyani; Ismail, Rita; Puteri, Tiara Primanda; Deswani, Deswani (Jurnal Keperawatan, 2024)
Preparedness for menarche can be achieved by providing information and attention to young women when facing menarche so that they will be calmer and ready to welcome the arrival of menarche. The initial survey, conducted by the researchers using an interview method involving four elementary school students who had experienced menarche, revealed that they experienced panic and embarrassment when facing menarche. They did not obtain information on menarche from their parents (mothers). Several findings have shown that their readiness to face menarche is still low. Mothers' awkwardness in providing information directly to young women can be overcome by using media in the form of e-mobiles or the internet. A pre-experiment using a single-group pretest-posttest methodology without a control group is the type of study design that will be used. The study variable was teenage girls' knowledge of reproductive health in preparation for menarche. A t-test was used for data analysis. The study was conducted between March and December 2023. SD Negeri 07 Pagi in the Ciracas District of East Jakarta served as the research site. The study population consisted of female pupils in classes 3, 4, 5, and 6 who had not yet reached menarche. Adolescent reproductive health, young women's preparation for menarche, and views on the usage of menarche information were the topics covered in the questionnaire. The initial readiness variable (pre-test) of young women and the results of the readiness (post-test) of young women after obtaining reproductive health information using the women's menarche information application obtained a Sig. (2-tailed) of 0.000 < α (0.05), as did the Paired T-test of the initial understanding variable (pre-test) of teenage girls with the variable of understanding results (post-test) of teenage girls. Young women's pre- and post-test understandings and readiness differed significantly from one another. They also differed significantly from one another in terms of their initial readiness and subsequent readiness following the use of the menarche information application to obtain reproductive health information.